Evaluation of strontium-containing PCL-PDIPF scaffolds for bone tissue engineering: In vitro and in vivo studies - Lino, Agustina Berenice (2018)
Bone tissue engineering (BTE) has the general objective of restoring and improving damaged bone. A very interesting strategy for BTE is to combine an adequate polymeric scaffold with an osteoinductive compound. Strontium is a divalent cation that can substitute calcium in hydroxyapatite and induce both anabolic and anti-catabolic effects in bone. On the other hand, systemic increases in Sr 2+ levels can provoke adverse cardiovascular effects. In the present study we have developed a compatibilized blend of poly-ε-caprolactone (PCL) and polydiisopropyl fumarate (PDIPF) enriched with 1% or 5% Sr 2+ and evaluated the applicability of these biomaterials for BTE, both in vitro and in vivo. In vitro, whereas Blend + 5% Sr 2+ was pro-inflammatory and anti-osteogenic, Blend + 1% Sr 2+ released very low quantities of the cation; was not cytotoxic for cultured macrophages; and showed improved osteocompatibility when used as a substratum for primary cultures of bone marrow stromal cells. In vivo, implants with Blend + 1% Sr 2+ significantly increased bone tissue regeneration and improved fibrous bridging (vs. Blend alone), while neither inducing a local inflammatory response nor increased serum levels of Sr 2+ . These results indicate that our compatibilized blend of PCL-PDIPF enriched with 1% Sr 2+ could be useful for BTE.